Analysis of Human Capital Plan Implementation In Improving Human Resource Performance at PT Furnimate Creation (PT FMC) - Ilham Baihaqi Baharsyah; Rhian Indradewa; Muhammad Dhafi Iskandar; Unggul Kustiawan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the implementation of a human capital plan to support the effectiveness of human resource management at PT Furnimate Creation (PT FMC), a furniture and interior design company. The background of this study is based on the importance of human resources as a strategic asset in creating competitive advantage, as well as the existence of a research gap that shows that studies related to the implementation of an integrated human capital plan in project-based and customization companies are still limited. This study uses a qualitative approach with descriptive methods. Data were collected through in-depth interviews, observations, and documentation, involving the company's management and employees. Data analysis techniques were carried out using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources, techniques, and time. The results of the study indicate that the implementation of the human capital plan at PT Furnimate Creation (PT FMC) has been carried out in a structured manner through aspects of competency-based recruitment, employee training and development, performance assessment using a balanced scorecard approach, and a compensation system tailored to employee contributions. This implementation has been proven to support increased employee productivity and performance. However, several obstacles remain, such as limitations in the development of specialist competencies and the suboptimal integration between HR planning and the company's business strategy. The conclusions of this study indicate that human capital planning plays a crucial role in improving the effectiveness of HR management and supporting organizational sustainability. Therefore, a more integrated and long-term HR development strategy is needed to enhance company competitiveness.